Navigating Financial Fortitude: Insights from 2020-2022 Performance Analysis: Menapaki Ketangguhan Keuangan: Wawasan dari Analisis Kinerja 2020-2022 - Sulkifli; Machmud, Mulyana; Hasan, Hamida (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the financial performance of a company across 2020-2022, focusing on liquidity, solvency, and profitability ratios through quantitative descriptive methods. Data from financial statements accessed via the Indonesia Stock Exchange's official website forms the basis of analysis. The research reveals promising indicators in the company's profitability, marked by increased sales, reduced operational expenses, and improved cash flow. Despite these positive trends, the company maintains its capacity to meet financial obligations. These findings suggest a commendable operational efficiency and financial health within the studied period, indicating potential avenues for further analysis and strategic decision-making in similar industries. Highlights: Quantitative Analysis: Utilized numerical data for comprehensive evaluation. Profitability Indicators: Highlighted increased sales and reduced expenses. Financial Health: Demonstrated the company's ability to meet obligations. Keywords: Financial Performance, Ratio Analysis, Quantitative Methods, Profitability, Liquidity